2020
DOI: 10.3390/nu12092496
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Mechanisms Mediating Adaptation to Low-Carbohydrate, High-Fat Diets during Exercise Training

Abstract: Interest in low-carbohydrate, high-fat (LCHF) diets has increased over recent decades given the theorized benefit of associated intramuscular adaptations and shifts in fuel utilization on endurance exercise performance. Consuming a LCHF diet during exercise training increases the availability of fat (i.e., intramuscular triglyceride stores; plasma free fatty acids) and decreases muscle glycogen stores. These changes in substrate availability increase reliance on fat oxidation for energy production while simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…In order to be utilized as a metabolic substrate for energy expenditure, ketone bodies are excreted by the liver to the bloodstream and reconverted into acetyl-CoA in extrahepatic organs, and thereafter are incorporated into the TCA cycle for terminal oxidation [ 192 ]. Therefore, ketone bodies are widely recognized as an alternative source of energy for highly aerobic metabolic organs such as the brain, skeletal muscle, and heart, particularly when carbohydrate availability is deficient or during periods of negative energy balance accounting for approximability 185 g/day as seen in fasting and starvation states, low carbohydrate high fat ketogenic diets or during prolonged endurance exercise [ 191 , 193 , 194 ]. The metabolic contribution of ketone bodies as a potent metabolic fuel for energy expenditure during exercise and physical activity is an area of increasing attention in the field of exercise physiology and sport nutrition in recent years.…”
Section: Other Energy Provision Sourcesmentioning
confidence: 99%
“…In order to be utilized as a metabolic substrate for energy expenditure, ketone bodies are excreted by the liver to the bloodstream and reconverted into acetyl-CoA in extrahepatic organs, and thereafter are incorporated into the TCA cycle for terminal oxidation [ 192 ]. Therefore, ketone bodies are widely recognized as an alternative source of energy for highly aerobic metabolic organs such as the brain, skeletal muscle, and heart, particularly when carbohydrate availability is deficient or during periods of negative energy balance accounting for approximability 185 g/day as seen in fasting and starvation states, low carbohydrate high fat ketogenic diets or during prolonged endurance exercise [ 191 , 193 , 194 ]. The metabolic contribution of ketone bodies as a potent metabolic fuel for energy expenditure during exercise and physical activity is an area of increasing attention in the field of exercise physiology and sport nutrition in recent years.…”
Section: Other Energy Provision Sourcesmentioning
confidence: 99%
“…Intramuscular fat (IMF) is an essential reference for measuring meat quality. The content of IMF can directly affect various meat traits and further determine the price of meat products. , The proper quantity and distribution of IMF can enhance meat flavor and palatability . In adipose tissue, the main source of lipid deposition is the differentiation of adipocytes, a complex network system regulated by various cytokines or signal pathways .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, previous studies demonstrated that short and longer‐term HFD increases both EI and EE, with augmented fat oxidation and consequently reduced RER (Brown et al, 1985 ; Burke et al, 2021 ; Che et al, 2021 ; Gregory et al, 2011 ; Hansen et al, 2007 ; Helge et al, 2001 ; Sasaki et al, 2014 ). This is driven by increased utilization of intramuscular and plasma triglyceride/non‐esterified fatty acids stores (Helge et al, 2001 ; Howard & Margolis, 2020 ). These observations were confirmed in mouse models (Brown et al, 1985 ; Sasaki et al, 2014 ) as well as in human studies (Burke et al, 2021 ; Che et al, 2021 ; Gregory et al, 2011 ; Hansen et al, 2007 ; Helge et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Longer adaptation to HFD in a 7 weeks study resulted in increased fat oxidation during aerobic exercise in untrained male participants, attributed to utilization of plasma triglycerides (Helge et al, 2001 ). Taken together, HFD increases reliance on fat oxidation, and decreases carbohydrate oxidation during submaximal exercise, demonstrating a close link between dietary composition and skeletal muscle fuel selection during exercise (Howard & Margolis, 2020 ).…”
Section: Introductionmentioning
confidence: 99%